Burden of Coronary Artery Disease and Peripheral Artery Disease: A Literature Review - Rupert Bauersachs; Uwe Zeymer; Jean-Baptiste Brière; Caroline Marre; Kevin Bowrin; Maria Huelsebeck (Cardiovascular Therapeutics)
Background. Atherothrombotic disease, including coronary artery disease (CAD) and peripheral artery disease (PAD), can lead to cardiovascular (CV) events, such as myocardial infarction, stroke, limb ischemia, heart failure, and CV death. Aim. Evaluate the humanistic and economic burden of CAD and PAD and identify unmet needs through a comprehensive literature review. Methods. Relevant search terms were applied across online publication databases. Studies published between January 2010 and August 2017 meeting the inclusion/exclusion criteria were selected; guidelines were also included. Two rounds of screening were applied to select studies of relevance. Results. Worldwide data showed approximately 5–8% prevalence of CAD and 10–20% prevalence of PAD, dependent on the study design, average age, gender, and geographical location. Data from the REACH registry indicated that 18–35% of patients with CAD and 46–68% of patients with PAD had disease in one or more vascular beds. Use of medication to control modifiable CV risk factors was variable by country (lower in France than in Canada); statins and aspirin were the most widely used therapies in patients with chronic disease. Survival rates have improved with medical advancements, but there is an additional need to improve the humanistic burden of disease (i.e., associated disability and quality of life). The economic burden of atherothrombotic disease is high and expected to increase with increased survival and the aging population. Conclusion. CAD and PAD represent a substantial humanistic and economic burden worldwide, highlighting a need for new interventions to reduce the incidence of atherothrombotic disease.